Analysis of Venusian Wrinkle Ridge Morphometry Using Stereo‐Derived Topography: A Case Study From Southern Eistla Regio. Issue 5 (11th May 2022) - Bethell, E. M.; Ernst, R. E.; Samson, C.
Abstract: We present an analysis of 503 topographic profiles taken across 40 ENE‐WSW trending wrinkle ridges from Southern Eistla Regio, Venus, using stereo‐derived topography. We find that their average widths and heights are on the order of 10 km and 100 m, respectively. While the majority of the wrinkle ridges are asymmetric and display vergence to the southeast, some are quasi‐symmetric, possibly representing pop‐up structures, and possess multiple peaks along the backslope, potentially indicating the presence of secondary backthrust faults. Fault geometry modeling in which the average observed wrinkle ridge topographic profile is matched to the calculated surface deformation while varying various faulting parameters indicates that the wrinkle ridges studied have dips of 30°, penetrate to depths of 5 km or less, are blind and reach to within 2 km of the surface, have accommodated approximately 200 m of slip, and possess a planar geometry. These results imply that the wrinkle ridges formed through a thin‐skinned deformation style. The spacing and distribution of the wrinkle ridges at a regional scale displays a clear relationship between wrinkle ridge deformation and lithospheric properties. We therefore conclude that the distribution of wrinkle ridges in the study area is a direct reflection of the regional strain which, in turn, is a result of mantle dynamics coupled with lithospheric thickness. The accumulation of contractional deformation expressed as wrinkle ridges appears to be the result of mantle downwelling along the peripheries of Eistla Regio. Plain Language Summary: The topography of sinuous ridges (referred to as "wrinkle ridges") on the surface of Venus has not been well studied due to the low resolution of the topography data collected by the Magellan mission. A topography data set that was recently created using data from two different cycles of Magellan radar imaging ("stereo‐derived topography") has provided higher resolution topography of the surface. We used these data to study the shape of wrinkle ridges on Venus in a study area that is located to the south of Eistla Regio. We studied the width, height, and degree of symmetry of the wrinkle ridges and found that on average, they are approximately 10 km wide, 100 m high, and slightly asymmetric. By modeling the wrinkle ridges as thrust faults (breaks in the crust where rocks on one side have been thrust above the other side), we find that the faults are confined to shallow depths in the crust, do not reach the surface, and have undergone approximately 200 m of movement along the fault's surface. We also found that regions of closely spaced wrinkle ridges in the study area coincide with areas of thinner crust. Key Points: Wrinkle ridges in Southern Eistla Regio, Venus, have been revealed to have widths and heights of approximately 10 km and 100 m, respectively Modeling suggests thrust faults are planar, have dips of 30°, reach depths of 5 km, are blind to 2 km, and had 200 m of slip The spatial distribution of wrinkle ridges is correlated negatively with the crustal thickness